Students' Playful Tactics. Issue 6 (3rd February 2015) - Rust, Julie
Abstract By examining the ways in which high school students in two different English classes take up virtual self‐representation tactics in school‐based social networking sites, this article explores how young people carefully juggle the digital identities they adopt for the eyes of both peers and teachers. The data reveals that the students' cultivation of selves are influenced by the affordances of the spaces they inhabit, and that the specific features of the online class network initiated three identity‐shaping tactics: inserting popular culture, adding humor, and engaging in gossip. Because these themes of self are distinct from the identity themes that typically emerge when students write traditional essays for English class, this work highlights the fact that educators face new challenges and opportunities when making room for informal, social digital spaces for curricular purposes.